2020
DOI: 10.1055/a-1301-3841
|View full text |Cite
|
Sign up to set email alerts
|

A neural network-based algorithm for assessing the cleanliness of small bowel during capsule endoscopy

Abstract: Background and Aims. Cleanliness scores in small bowel (SB) capsule endoscopy (CE) have poor reproducibility. The aim of this study was to evaluate a neural network (NN)-based algorithm for automated assessment of the SB cleanliness during CE. Methods: First, 600 normal third-generation SBCE still frames were categorized as “adequate” or “inadequate” in terms of cleanliness by three expert readers, according to a 10-point scale and served as a training database. Then, 156 third-generation SBCE recordings were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 15 publications
0
24
0
Order By: Relevance
“…By dividing the gastrointestinal tract cleanliness into four grades (poor, general, good, and excellent), the objective and automatic cleanliness evaluation were realized, and a good classification accuracy (95.23%) was achieved [52]. On the field of cleanliness assessment of small-bowel capsule endoscopy, Romain Leenhardt et al also reported an accuracy of 89.7% to determine whether the bowel preparation is enough or not [53]. Another major problem of capsule endoscopy is the retention at the gastroduodenal junction.…”
Section: Discussionmentioning
confidence: 99%
“…By dividing the gastrointestinal tract cleanliness into four grades (poor, general, good, and excellent), the objective and automatic cleanliness evaluation were realized, and a good classification accuracy (95.23%) was achieved [52]. On the field of cleanliness assessment of small-bowel capsule endoscopy, Romain Leenhardt et al also reported an accuracy of 89.7% to determine whether the bowel preparation is enough or not [53]. Another major problem of capsule endoscopy is the retention at the gastroduodenal junction.…”
Section: Discussionmentioning
confidence: 99%
“…Bowel cleanliness is a crucial point and different scales are now adopted for colonoscopy. In the context of SBCE, two most recent AI‐based algorithms have been proposed 34,35 . Both showed that AI can lead to a robust and reliable cleanliness metric at image level.…”
Section: Assessment Of Bowel Cleanlinessmentioning
confidence: 99%
“…Both showed that AI can lead to a robust and reliable cleanliness metric at image level. A recent contribution shows that the principle of DL approaches can be extended to the video level 35 . In the context of SBCE, two most recent AI‐based algorithms have been proposed (Table 2).…”
Section: Assessment Of Bowel Cleanlinessmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach sets the scene for structured delivery of a series of much-needed solutions for accurate detection and characterization of abnormal CE findings. These include reliably producing thumbnails of anatomical landmarks (i. e. stomach, small bowel, colon), which is of tremendous importance especially with the emerging trend of panenteric CE 7 ; reproducible assessment of bowel cleanliness 8 , which can easily surpass that of human readers 9 , thus allowing crucial decisions to be made on repeating a procedure; and, crucially, the relevance of findings according to the clinical setting 10 .…”
mentioning
confidence: 99%